HIGH DIETARY CARBOHYDRATE AND PANCREATIC LESION - Novelli, ELB; Rodrigues, N. L.; Franca, E. L.; Gebra, LMM; Ribas, B. O. (Associação Brasileira de Divulgação Científica (ABRADIC), 1993)
The ability of high dietary carbohydrate to induce acute pancreatitis was investigated in groups of 16,2 1-day and 15-month old rats fed different carbohydrate diets for 30 days. Significantly increased levels of serum amylase (2-fold), phospholipids (50%),phosphorus (2-fold), and lipoperoxides (8-fold) were observed in 15-month old rats fed a high-carbohydrate diet, compared to rats fed a diet with normal carbohydrate levels, indicating peroxidation of membrane lipids which caused final cell death and pancreatic lesion. Serum Cu-Zn superoxide dismutase activity was not altered. Daily administration of bovine Cu-Zn superoxide dismutase conjugated with polyediylene glycol prevented the serum level alterations and pancreatic lesions, indicating that the superoxide radical has a role in dietary carbohydrate-induced acute pancreatitis. No biochemical changes were observed in rats in which treatment was initiated on the 21st day of life indicating that this is an age-related lesion.
Keywords: CARBOHYDRATE; PANCREATIC LESION; SUPEROXIDE DISMUTASE